Behavioural responses of shallow-water benthic marine scavengers to fish carrion: a preliminary study. Issue 5 (2nd September 2016) - Davenport, J.; McCullough, S.; Thomas, R. W.; Harman, L.; McAllen, R.
Abstract: Observations of the behavioural responses of near-shore marine scavengers to fish carrion were made at two depths (1–2 m, 16–18 m). Gobies and juvenile whelks were the most numerous scavengers, but appeared to consume little biomass. The first scavengers to appear at carrion (seconds/minutes) were swimming forms, later (minutes) joined by fast-moving, crawling portunid crabs. Large scavengers (crabs/starfish/catsharks) arrived after tens of minutes/hours. Scavengers were 'direct feeders' on the bait (crabs and some fish) or 'indirect feeders' (gobies and whelks) on scraps generated by direct feeders. Scavengers spent little time in aggression. While fish spent relatively low proportions of their time feeding (e.g. Lipophrys pholis : 2.2–15.8%), crabs fed almost continuously (e.g. Carcinus maenas : 97.8–99.3%) before leaving baits. Crab presence depressed fish feeding. Crabs were wasteful feeders that macerated the baits, generating scraps for indirect feeders and attracting more scavengers. Large scavengers consumed most bait.